2016
DOI: 10.1212/wnl.0000000000003148
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of thrombolysis in telestroke

Abstract: URL: http://www.crd.york.ac.uk/PROSPERO. Unique identifier: CRD42015017232.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 33 publications
3
79
0
2
Order By: Relevance
“…Telestroke has brought IVT and stroke neurologist's expert consultation closer to the patients. Safety and efficacy of fibrinolysis delivered through telestroke networks in the 3-h window has been demonstrated in a recent meta-analysis including 7 studies [3]. However, due to the high beneficial effect of early endovascular treatment in patients with large vessel occlusion [4], a debate exists on whether transferring selected acute stroke patients directly from the field to the closest center with endovascular treatment capabilities determines a better prognosis than transferring them to a local center able to administer IVT [5].…”
Section: Introductionmentioning
confidence: 98%
“…Telestroke has brought IVT and stroke neurologist's expert consultation closer to the patients. Safety and efficacy of fibrinolysis delivered through telestroke networks in the 3-h window has been demonstrated in a recent meta-analysis including 7 studies [3]. However, due to the high beneficial effect of early endovascular treatment in patients with large vessel occlusion [4], a debate exists on whether transferring selected acute stroke patients directly from the field to the closest center with endovascular treatment capabilities determines a better prognosis than transferring them to a local center able to administer IVT [5].…”
Section: Introductionmentioning
confidence: 98%
“…Using a camera and having access to brain computed tomography (CT), neurologists at remote sites were able to determine whether a patient would be candidate for reperfusion treatment with intravenous thrombolysis. It was subsequently shown that telestroke achieved similar safety and outcome results to those in comprehensive stroke centers . Importantly, however, acute stroke treatment has changed dramatically over the last few years, endovascular thrombectomy (EVT) is now the standard of care in large vessel occlusion (LVO) strokes.…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently shown that telestroke achieved similar safety and outcome results to those in comprehensive stroke centers. [2][3][4] Importantly, however, acute stroke treatment has changed dramatically over the last few years, endovascular thrombectomy (EVT) is now the standard of care in large vessel occlusion (LVO) strokes.…”
Section: Introductionmentioning
confidence: 99%
“…76 In another study on a large telestroke cohort in the Delaware valley, the differences between patients transferred and non-transferred to a primary stroke care center ter. 79 The strategy consisting in the initiation of thrombolytic treatment in a spoke hospital under the guidance provided by a specialist located in a central hospital using telemedicine facilities, followed by the transfer of patient to the central hospital, has been named the "drip and ship" strategy and proved to provide outcomes comparable to those obtained using treatment directly in the central hospital. 80 In addition, a study by Heffner et al…”
Section: Telestroke Networkmentioning
confidence: 99%